2019
DOI: 10.3390/d12010011
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling the Effects of Disturbance from Those of Dominant Tall Grass Features in Driving the Functional Variation of Restored Grassland in a Sub-Mediterranean Context

Abstract: Land abandonment in sub-Mediterranean grasslands causes the spread of tall-grasses, affecting biodiversity and ecosystem functioning. Mowing allows the recovery of the coenological composition after invasion, but the mechanisms acting at the fine-scale are poorly investigated. Since 2010 in the Central Apennines, we fenced a grassland invaded by Brachypodium rupestre, divided it into two areas, half of each was mowed biyearly and half remained unmown. In 2017 we selected ten 20 × 20 cm experimental units per h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 49 publications
(66 reference statements)
1
19
0
Order By: Relevance
“…The strong diffusion of B. genuense on habitat 6210* is probably due to the variation in the livestock types (from sheep to cows/horses) and/or the reduction of extensive grazing in the study area. The increase of Brachypodium (B. pinnatum, B. genuense, B. rupestre) distribution cause a reduction in grasslands biodiversity [31,33,92,107,108]. As shown in a recent study [109], when B. genuense and/or B. rupestre becomes dominant (cover > 80%), a substantial reduction in biodiversity was observed.…”
Section: Discussionmentioning
confidence: 94%
“…The strong diffusion of B. genuense on habitat 6210* is probably due to the variation in the livestock types (from sheep to cows/horses) and/or the reduction of extensive grazing in the study area. The increase of Brachypodium (B. pinnatum, B. genuense, B. rupestre) distribution cause a reduction in grasslands biodiversity [31,33,92,107,108]. As shown in a recent study [109], when B. genuense and/or B. rupestre becomes dominant (cover > 80%), a substantial reduction in biodiversity was observed.…”
Section: Discussionmentioning
confidence: 94%
“…To understand the functional trajectory of the plant community induced by mowing twice a year, we selected a core of plant traits capturing different functional dimensions: competition for light and space occupation (plant vegetative height, H; horizontal architecture, HA) [52,53]; resource exploitation (specific leaf area, SLA; leaf dry matter content, LDMC) [53] and regulation of leaf temperature and water-use efficiency during photosynthesis (leaf area, LA) [53]; temporal niche exploitation (flowering phenology, FP; leaf phenology, LP) [27,52]; clonal strategy (clonal position, CP; clonal spread, CS) (adapted from [54]). Moreover, leaf traits (LA, SLA, and LDMC) were also used to calculate plant CSR (competitive, stress tolerant, and ruderal) strategies [39], by integrating both leaf economics (typical of S and R strategy selection) and leaf size (typical of the C strategy) variation spectra in a three-way trade-off [36].…”
Section: Data Collectionmentioning
confidence: 99%
“…Moreover, leaf traits (LA, SLA, and LDMC) were also used to calculate plant CSR (competitive, stress tolerant, and ruderal) strategies [39], by integrating both leaf economics (typical of S and R strategy selection) and leaf size (typical of the C strategy) variation spectra in a three-way trade-off [36]. These selected traits are related to both competitive ability and response to mowing [52][53][54][55]. A description of each trait and their respective list of states and data sources are reported in Table 1.…”
Section: Data Collectionmentioning
confidence: 99%
“…In particular, Tordoni et al [3] suggested that functional niche divergence may foster community invasibility; resident native communities more susceptible to invasion are those which, on average, showed a combination of functional traits (higher resource acquisition capacity and lower drought resistance) coupled with an apparently reduced water-use efficiency. In a similar way, land-use change can trigger processes that transform the landscape [17]: land abandonment in sub-Mediterranean grasslands causes the spread of native tall-grasses, affecting biodiversity and ecosystem functioning [19]. At a fine scale, mowing is used to allow the recovery of the coenological composition after invasion, acting as an abiotic filter (enhancement of tolerance-avoidance strategies); the reduction of weaker competitors increases the functional variation between coexisting species.…”
Section: Global Threats and Challengesmentioning
confidence: 99%
“…At a fine scale, mowing is used to allow the recovery of the coenological composition after invasion, acting as an abiotic filter (enhancement of tolerance-avoidance strategies); the reduction of weaker competitors increases the functional variation between coexisting species. Understanding the mechanism that enhances the extent of functional strategies related to resource acquisition and storage, reproduction, space occupation, and temporal niche exploitation [19][20][21] can help us to answer global challenges.…”
Section: Global Threats and Challengesmentioning
confidence: 99%